Urinary retinol binding protein predicts renal outcome in systemic immunoglobulin light‐chain (AL) amyloidosis. (9th August 2021) - Rezk, Tamer; Salota, Rashim; Gan, Jaslyn J.; Lachmann, Helen J.; Fontana, Marianna; Siew, Keith; Martinez‐Naharro, Ana; Guillotte, Christianne; Bass, Paul; Sachchithanantham, Sajitha; Mahmood, Shameem; Petrie, Aviva; et al.
Summary: Renal risk stratification in systemic immunoglobulin light‐chain (AL) amyloidosis is according to estimated glomerular filtration rate (eGFR) and urinary protein creatinine ratio (uPCR), the latter attributed to glomerular dysfunction, with proximal tubular dysfunction (PTD) little studied. Urinary retinol binding protein 4 (uRBP), a low molecular weight tubular protein and highly sensitive marker of PTD, was prospectively measured in 285 newly diagnosed, untreated patients with systemic AL amyloidosis between August 2017 to August 2018. At diagnosis, the uRBP/creatinine ratio (uRBPCR) correlated with serum creatinine ( r  = 0·618, P  < 0·0001), uPCR ( r  = 0·422, P  < 0·0001) as well as both fractional excretion of phosphate and urate ( r  = 0·563, P  < 0·0001). Log uRBPCR at diagnosis was a strong independent predictor of end‐stage renal disease {hazard ratio [HR] 2·65, [95% confidence interval (CI) 1·06–6·64]; P  = 0·038}, particularly in patients with an eGFR >30 ml/min/1.73 m 2 [HR 4·11, (95% CI 1·45–11·65); P  = 0·008] and those who failed to achieve a deep haematological response to chemotherapy within 3 months of diagnosis [HR 6·72, (95% CI 1·83–24·74); P  = 0·004], and also predicted renal progression [HR 1·91, (95% CI 1·18–3·07); P  = 0·008]. Elevated uRBPCR indicates PTD and predicts renal outcomes independently of eGFR, uPCR and clonal response in systemic AL amyloidosis. The role of uRBPCR as a novel prognostic biomarker merits further study, particularly in monoclonal gammopathies of renal significance.